2014
DOI: 10.1038/ncomms6587
|View full text |Cite
|
Sign up to set email alerts
|

A far-off-resonance optical trap for a Ba+ ion

Abstract: Optical trapping and ions combine unique advantages of independently striving fields of research. Light fields can form versatile potential landscapes, such as optical lattices, for neutral and charged atoms, while avoiding detrimental implications of established radiofrequency traps. Ions interact via long-range Coulomb forces and permit control and detection of their motional and electronic states on the quantum level. Here we show optical trapping of 138 Ba þ ions in the absence of radio-frequency fields vi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
67
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 52 publications
0
67
1
1
Order By: Relevance
“…In the present study, however, we consider the scenario for which the ion is tightly confined (i.e, in traps with frequencies ω 2π 100 kHz), such that its motion can be discarded. Apart from simplifying the scattering problem, we underscore that such condition can be fulfilled in current experiments (e.g., with optical traps [25] or Paul traps, where frequencies can even reach the MHz range [26]). Let us note that CIRs in atomic systems have attracted great interest, as they can be used to control the atom-atom interaction [27][28][29], e.g., for realising the so-called Tonks-Girardeau gas [30,31] and the excited many-body phase known as the super-Tonks-Girardeau gas [32].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, however, we consider the scenario for which the ion is tightly confined (i.e, in traps with frequencies ω 2π 100 kHz), such that its motion can be discarded. Apart from simplifying the scattering problem, we underscore that such condition can be fulfilled in current experiments (e.g., with optical traps [25] or Paul traps, where frequencies can even reach the MHz range [26]). Let us note that CIRs in atomic systems have attracted great interest, as they can be used to control the atom-atom interaction [27][28][29], e.g., for realising the so-called Tonks-Girardeau gas [30,31] and the excited many-body phase known as the super-Tonks-Girardeau gas [32].…”
Section: Introductionmentioning
confidence: 99%
“…Since direct laser cooling of molecules is impractical due to their internal rotational and vibrational (ro-vibrational) degrees of freedom, a number of different approaches that allow production of ultracold samples of selected dimers have been developed [1,2]. Recent advances in trapping and laser-cooling ions to ultracold temperatures [3][4][5][6][7][8][9] allow experimenting with hybrid systems composed of overlapping trapped cold atomic gases with ultracold ions [10]. Such systems offer opportunities for new developments in the field of ultracold quantum matter, with a benefit of simpler and more reliable trapping than it is available for neutral molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the induced dipole interaction of the atom with the ion displaces the ion from the RF null, causing it to undergo micromotion; the subsequent collision with the atom causes an interruption of this micromotion during which energy from the RF drive can be converted to incoherent kinetic energy, and, on average, leads to heating rates generally prohibitive to reaching the quantum regime of atom-ion interactions. Cetina et al [143] showed that the regime of single-partial-wave atom-ion interaction could only be reached for large ion-atom mass ratio (such as Yb + and Li), weak RF traps, and state-of-the-art control over DC electric fields on the order of 10 mV/m (as recently achieved in [136]). …”
Section: A Versatile Rf-free Trap: Ions In An Optical Latticementioning
confidence: 99%
“…The deep optical potentials required to confine a charged particle against stray fields impart significant recoil heating [133,136], especially when a relatively small detuning to atomic resonance is required due to limited laser power. The large optical fields required also cause significant light shifts on the atomic transitions, limiting the cooling efficiency of typical techniques, such as Doppler cooling [135], and to a lesser degree resolvedsideband cooling.…”
Section: A Versatile Rf-free Trap: Ions In An Optical Latticementioning
confidence: 99%
See 1 more Smart Citation